Civil Service Reform : Strengthening World Bank and IMF Collaboration - World Bank (Washington, DC, 2013)
This report sets out the principal aspects of civil service reform that were discussed at a workshop for the World Bank and International Monetary Fund staff on September 2, 2001. The objective of the workshop was to strengthen collaboration between the Bank and the Fund in order to achieve greater effectiveness in Bank- and Fund-supported programs in this area. The workshop concluded that strengthened collaboration between the Bank and the Fund should ensure consistency between the sometimes-conflicting goals of short-term fiscal discipline and longer-term structural reforms supported by Fund and Bank programs. After the introduction, section 2 presents an overview of the major objectives of civil service reform, highlighting some of the core macrofiscal and structural perspectives. Section 3 follows, and highlights recent Bank- and Fund-supported programs that address civil service reform. Section 4 considers the effectiveness of Bank and Fund interventions, noting the intrinsic tensions between reform objectives and the politically challenging nature of civil service reforms. Section 5 considers how the two organizations have worked, both individually and in tandem. This section also offers conclusions and proposals for improving the effectiveness of Bank-Fund interventions in civil service reform.